Spatial and seasonal variations of chlorophyll a in Zhanjiang Bay, China, and controlling factors - Wang, Shuangling; Zhou, Fengxia; Chen, Fajin; Zhu, Qingmei; Meng, Yafei (Frontiers in Marine Science, 2024)
Based on on-site survey data from 26 stations in the surface seawater of Zhanjiang Bay in April (spring), July (summer), September (autumn), and December (winter) of 2017, the spatial distribution characteristics of chlorophyll a (Chl a) and nutrients in the surface seawater of Zhanjiang Bay in different seasons were analyzed, and the regulatory mechanism of chlorophyll a spatiotemporal changes was discussed. The results showed that the Chl a concentrations in the surface water of Zhanjiang Bay are 0.44–37.43 μg/L, and are highest in summer and lowest in spring (summer: 11.6 µg/L; winter: 11.5 µg/L; autumn: 10.7 µg/L; spring: 1.8 µg/L). The spatial distribution of surface seawater Chl a in different seasons shows an opposite trend to the spatial distribution of nutrients. The study revealed that the low Chl a concentration in spring is mainly limited by SiO3-Si, while the high Chl a concentration in winter is closely related to climate conditions and coastal currents. This study suggests that based on the influence of monsoon climate and land rainfall erosion, the particulate organic carbon (POC) in Zhanjiang Bay in spring and summer is derived from land-based inputs, while in autumn and winter, the POC in the surface water of Zhanjiang Bay is mainly derived from in situ phytoplankton production. The dominant factors affecting the distribution of Chl a in the surface water of Zhanjiang Bay vary in different seasons, and are comprehensively influenced by terrestrial nutrient transport, artificial aquaculture, climate conditions, hydrodynamic conditions in the bay, and the coastal current of western Guangdong outside of the bay. The results of this study can provide scientific basis for improving the environment of Zhanjiang bay.